Sublimitas Supra-Dogma Hukum Adat dalam Hierarkhi Kaidah-kaidah Hukum Internasional - Bakir, Herman (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2018)
This descriptive research is specifically prepared to explore the dogma of Jus Cogens regarding its status as the highest legal source of International Customary Law, registering moments that the way this doctrine is institutionalized is such status; explore the ways in which Jus Cogens is applied to solving international disputes. The approach used to approach the object under study is a juridical-dogmatic approach, an approach commonly used in Legal Dogmatic studies in general. Meanwhile, the research method used in the overall context of this research is the normative-doctrinal legal research method. This is the name for the system that will teach this research to map core issues; collect data; and, information, conduct analysis, and then draw a set of conclusions. The Results: (a) Jus Cogens is a dogma that was born and developed from International Customs Law; (b) Jus Cogens has been accepted/adopted as the Highest Norm in the tradition of International Law; and, (c) Jus Cogens has been applied for the first time in resolving disputes between Bosnia and Herzegovina v. Montenegro Serbia.